2020
DOI: 10.1101/2020.03.27.011601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of Activating Transcription Factor 3 prevents KRAS-mediated pancreatic cancer

Abstract: The unfolded protein response (UPR) is activated in pancreatic pathologies and suggested as a target for therapeutic intervention. In this study, wxe examined Activating Transcription Factor 3 (ATF3), a mediator of the UPR which promotes acinar-to-ductal metaplasia (ADM) in response to pancreatic injury. Since ADM is an initial step in the progression to pancreatic ductal adenocarcinoma (PDAC), we hypothesized ATF3 is required for initiation and progression of PDAC. We generated mice carrying a germ line mutat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In all those cases, Atf3 loss exacerbates the injury phenotype but is dispensable for homeostasis and embryonic development, just as we observed here in stomach and pancreas injury. A recent publication similarly showed that Atf3 loss leads to decreased ADM and that absence of Atf3 in a spontaneous cancer mouse model actually prevented KRAS G12D ‐driven pancreatic cancer (Azizi et al , 2021). That may be consistent with our results here, as mutant KRAS‐driven cancer depends on ADM, which depends on ATF3 and paligenosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In all those cases, Atf3 loss exacerbates the injury phenotype but is dispensable for homeostasis and embryonic development, just as we observed here in stomach and pancreas injury. A recent publication similarly showed that Atf3 loss leads to decreased ADM and that absence of Atf3 in a spontaneous cancer mouse model actually prevented KRAS G12D ‐driven pancreatic cancer (Azizi et al , 2021). That may be consistent with our results here, as mutant KRAS‐driven cancer depends on ADM, which depends on ATF3 and paligenosis.…”
Section: Discussionmentioning
confidence: 97%
“…Activating transcription factor 3 is a member of the ATF/CREB family of transcription factors and shares similar binding sites with AP‐1 (also from the ATF/CREB and c‐Fos/c‐Jun families), which regulates immediate early genes following stress/injury. Atf3 has been implicated in injury settings in many organs including cerebral ischemia (Wang et al , 2012), axon regeneration (Hunt et al , 2012; Gey et al , 2016), acute lung injury (Zhao et al , 2017), heart failure (Brooks et al , 2015), alcohol liver damage (Tsai et al , 2015), liver ischemia‐reperfusion injury (Zhu et al , 2018), stress‐induced β‐cell apoptosis (Hartman et al , 2004), ADM (Fazio et al , 2017; Azizi et al , 2021), and acute kidney injury (Li et al , 2010). ATF3 is also important for injury responses in Drosophila (Zhou et al , 2017) and Axolotl (Gerber et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We tested this hypothesis using our Kras wild-type, pancreas-specific Kdm6a-KO mice, namely Ptf1a Cre ;Kdm6a fl/fl , or Ptf1a Cre ;Kdm6a fl/Y (C-Kdm6a fl/ fl or C-Kdm6a fl/Y ) (Figure 12A), in a well-established, cerulein-induced, chronic pancreatitis model. 25 Mice were treated with cerulein for 2 weeks and then allowed to recover for 1 and 14 days (Figure 12B). There was a significant and persistent weight loss in female C-Kdm6a fl/fl mice at both day 1 and day 14 of recovery compared with the wild-type Ptf1a Cre ;Kdm6a þ/þ (C) Q26 mice (Figure 12C).…”
Section: Kdm6a Deficiency Alone Delays Recovery From Cerulein-induced Chronic Pancreatitismentioning
confidence: 99%